2021
DOI: 10.1007/s42452-021-04475-x
|View full text |Cite
|
Sign up to set email alerts
|

Metallic oxide–graphene composites as a catalyst for gas-phase oxidation of benzyl alcohol to benzaldehyde

Abstract: A new catalyst (FAG) composed of Fe, Al, and graphene (G) was prepared for catalyzing the reaction of benzyl alcohol (BA) to benzaldehyde (BD). The catalyst was characterized by XRD, XPS, SEM, and BET analyses. The catalytic performance of FAG for oxidation of BA to BD was studied by comparing with the catalysts ferrous oxide (Fe), ferrous oxide doped with aluminum (FA), and ferrous oxide doped with graphene (FG). The effects of amount of graphene additive, temperature, and ratio of Fe and Al were also studied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Gas-phase deposition methods involve introducing organometallic precursors in vapor phase for deposition onto graphene oxide surfaces [54][55][56][57][58]. Gas-phase deposition ensures uniform coating of graphene oxide with organometallic species, ensuring composite structural homogeneity [59,60].…”
Section: Influence On Composites Referencesmentioning
confidence: 99%
“…Gas-phase deposition methods involve introducing organometallic precursors in vapor phase for deposition onto graphene oxide surfaces [54][55][56][57][58]. Gas-phase deposition ensures uniform coating of graphene oxide with organometallic species, ensuring composite structural homogeneity [59,60].…”
Section: Influence On Composites Referencesmentioning
confidence: 99%
“…32 Sn species can induce the formation of hexagonal WO 3 with dominant exposed (001) and (200) planes, dramatically increase the specific surface area, change the structural properties and enhance the interactions between Sn–W oxides and RGO. 32 Li et al 33 found that Sn–W/RGO presented excellent catalytic properties for the reaction of BzOH to BzH. The BzOH conversion significantly increased, and the BzH selectivity reached 87.38%.…”
Section: Introductionmentioning
confidence: 99%
“…The BzOH conversion significantly increased, and the BzH selectivity reached 87.38%. 33 Ramirez-Barria et al 34 reported that Ru(CO)/NrGO (NrGO:N-doped reduced graphene oxide) displayed excellent BzOH conversions (50%) and BzH selectivity (>99%). The catalyst Ti(SO 4 ) 2 /GOF (Ti(SO 4 ) 2 : titanium sulfate; GOF: graphene oxide foam) showed unique catalytic activity (BzOH conversion 91.3%) and selectivity (99.0%) for the oxidation of BzOH to BzH using THF as solvent and H 2 O 2 as oxidant.…”
Section: Introductionmentioning
confidence: 99%